Pemberdayaan Ekonomi Keluarga Melalui Produksi Virgin Coconut Oil Berbasis Kearifan Lokal di Desa Pesisir Selayar - Nengsih, Ratika; Kasim, Sinta; Syahar, A Ulfah Tenripada (Pusat Pengembangan Pendidikan dan Bakat Indonesia/Education and Talent Development Center of Indonesia (ETDC Indonesia), 2026)
Garaupa Raya Village in Selayar Islands Regency faces economic challenges as a remote coastal area with limited infrastructure and underutilized coconut resources. This community empowerment program aimed to enhance family economic independence through Virgin Coconut Oil (VCO) production based on Islamic values and local wisdom. The program involved two main partners: PKK (Family Welfare Empowerment) with 22 active members and Youth Organization (Karang Taruna) with 10 members. Using Participatory Action Research approach, activities were conducted through five stages: socialization, technical and managerial training, appropriate technology implementation, monitoring and evaluation, and sustainability planning. The program provided semi-hydraulic coconut milk press equipment, fermentation containers, and digital marketing training. Results showed significant improvements: production capacity increased from 1-2 liters to 5-10 liters per month, 90% of members mastered simple bookkeeping, and products were marketed through TikTok and Shopee platforms under the brand